Perbedaan tingkat pengetahuan dan sikap sebelum dan sesudah penyuluhan HIV/AIDS dengan video - Mas Dwi Retna Ambarukma; Yani Widyastuti; Dyah Noviawati Setya Arum (Jurnal Kesehatan Ibu dan Anak, 2012)
Based on DJP3LKK report on 2011 of HIV/AIDS in lndonesia 2OO9 commutatively 25,18yo and increased to 33,5% in 2010, dominated by productive ages. One of the factors are less comprehensive of knowledge in HIV/AIDS BKKBN survey in 2008, there are 20,6% teenage had comprehensive knowledge. Education of HIV/AIDS used video is one of ways to give information. To increased knowledge and behavior toward preventing HIV/AIDS spreading. Purpose of this study to identify difference of knowledge level and behavior toward HIV/AIDS before and after health education using video in Highschool Sedayu 1 Bantul 2013. This study is quasi experiment with pretest-posttest with control group design. Sample of this study used purposive sampling; each group consist of 33 student. Data collecting used questioner. Data analyzed use paired t-test with significance 95%. The result are mean of pretest is 56,49 and behavior is 49,99. Mean of posttest in knowledge is 74,91 and behavior is 56,81 . Difference mean of knowledge are =18,42 and behaviour is =6,81 . From t-test, p-values treatment group (0,000) < 0,05 and p-value for control group (0,000) < 0,05.